Determinants of Green Purchasing Behavior : A Scoping Review - Anita Maulina; Nur Fitri Rahmawati; Budiana Ruslan; Yoka Mai Patria (School of Business, IPB University (SB-IPB), 2022)
The purpose of writing this article is to provide an understanding of the theory applied to green purchasing behavior. This study uses the scoping review method of compiling articles using discourse identification from various sources of descriptive analysis in the reviews related to green purchasing behavior. This scoping review has 6 stages where the last stage is optional. Scoping reviews need to be carried out in a study, but due to the lack of references related to the preparation of scoping reviews, many researchers do not understand how to prepare a scoping review that can help finding research novelty and research positions. The results of this study indicate that most studies identify green purchasing behavior tend to be organic product not only through attitudes, subjective norms, and perceived behavior control, but several other determinants can be studied or re-examined to identify the determinants of green purchasing behavior. The Theory of Planned Behavior has become a grand theory in several articles related to green purchasing behavior. Keywords: scoping review, green behavior, green purchasing behavior, theory of planned behavior, consumer behavior